Pemberdayaan Pokdarwis Desa Ngrupit Dalam Tata Kelola Usaha Wisata Edukasi Berbasis Etnomatematika - Dita Pebriyanti; Siti An Nisa; Fahim Khilda Afiffulloh; Dwi Wulan Sari; Nanda Bayu Aji Argananta; Abdullah Azzam; Efi Rahmayani; Siti Hafifah Komariah; Osfir Candikia Rara Komara; Alvian Bagas Adi Setiawan; Etika Oktaviani; Wahyu Riskina Dita; Satrio Nugroho; Uki Suhendar (Universitas Kristen Indonesia Toraja, 2023)
The development of Ngrupit Village as a tourism village is inseparable from the participation of all members of the community. One of the important elements in supporting the creation of a tourist village is the existence of an institution that can manage and organize tourism businesses or what we call a Tourism Awareness Group (Pokdarwis). This service activity aims to provide assistance to Pokdarwis Ngrupit Village to increase the understanding and capabilities of its members in tourism business governance. This service begins with the formation of Pokdarwis institutions, tourism potential survey activities, Forum Group Discussion (FGD) activities, and training in tourism business governance. Through this training activity, Pokdarwis of Ngrupit Village was given training, socialization, assistance, and empowerment regarding tourism business management, including financial management, marketing, facilities, and customer service. The benchmark for the success of this service activity is seen from the pre-test and post-test scores in the training activities. The results showed that the average pre-test score was 66.42 and the average post-test score was 87.14 in the tourism business management training. While in the training of Branding and Marketing of Tourism Businesses, the average pre-test score was 50.71 and post-test was 85.71. Based on these results, it was found that there was an increase in the average score before and after attending the training. Thus, this training increased the understanding of Pokdarwis members regarding tourism business management as well as branding and marketing of tourism businesses.